Toxicidade do cloridrato de doxorrubicina na dose de 120mg/m², em cadelas com tumor venéreo transmissível - Viéra, Rafaela Bortolotti [UNESP] (2015)
Doxorubicin (DOX) is considered one of the most active agent avaliable for chemotherapy treatment of cancer, in addition to be one of the most antineoplastic drug used for the treatment of canine Transmissible Venereal Tumor resistant to vincristine. For a better understanding of the side effects caused by the use of DOX in dogs, we did an study composed by 10 domestic, female, mixed breed dogs with Transmissible Venereal Tumor of natural ocurrence, diagnosed by cytology, with no evidence of metastasis and without previous chemotherapy treatment, that received DOX in dose of 30 mg/m² ou 1 mg/kg for animals weighing less than 15 kg. Were evaluated the effects of DOX in the peripheral blood and bone marrow, blood biochemistry and tumor cytotoxicity response. In order to standardize the toxicity level, we applied the terminology based on the addapted tables of the veterinary co-operative oncology group-Common terminology criteria for adverse events - VCOG-CTCAE). Statistical data were analyzed by the variance method with repeated measures; linear regression, quadratic and cubic and when there was a significant difference between means (P <0.05), these were compared by Tukey test. The values of red blood series did not change significantly between moments; the white blood cell count was significantly higher at baseline (M0) when compared to the 14th day after the fourth session (M7); segmented neutrophils had significant reduction on the 14th day after the first and third chemotherapy session when compared with the initial moment; lymphocytes, basophils, eosinophils and neutrophils rods did not differ between the moments. In The myelogram, rubrícitos, metarubrícitos ratio, showed a significant increase 21 days after the end of chemotherapy (M8), and myeloid: erythroid relationship showed significantly decreased after the treatment (M8); neutrophils rods and segmented neutrophils showed reduced values in M8. Biochemical parameters ...